Clinical and behavioral predictors of HIV-associated neurocognitive disorder among people with HIV who use substances: a secondary analysis of the HOPE trial - Gloria Wang; Xueying Yang; Kesheng Wang; Xiaoming Li; Zheng Dai; Shan Qiao (Journal of NeuroVirology, 2026)
This study examined behavioral, clinical, and hematologic factors associated with HIV-associated neurocognitive disorder (HAND) among people with HIV (PWH) using the International HIV Dementia Scale (IHDS) within a randomized clinical trial. This secondary analysis used data from the Hospital Visit as Opportunity for Prevention and Engagement for HIV-Infected Drug Users (HOPE) study, which enrolled 801 PWH who use substances from 11 U.S. hospitals. CD4 cell count, HIV-1 viral load, Global Severity Index (GSI), Global Assessment of Functioning (GAF), and Physical and Mental Component Scores (PCS, MCS) were assessed at baseline, 6 months, and 12 months. HAND was defined as an IHDS score ≤ 10. Multivariable linear and logistic regression models were used to identify baseline correlates of IHDS score and HAND, respectively. Linear mixed models were applied to evaluate the longitudinal changes in clinical outcomes. HAND prevalence was 76.3% (84.2% for females and 72.5% for males). Multivariable linear models revealed that obesity, CD4 cell counts < 200 cells/ µL, higher hemoglobin level and hematocrit, and higher GAF scores were significantly associated with IHDS score (p < 0.05). Furthermore, logistic models showed that recent alcohol use, obesity, viral suppression (≤ 200 copies/mL), hemoglobin and hematocrit levels, and GAF scores were associated with lower odds of HAND, whereas platelet count was linked to higher odds. Longitudinal analyses demonstrated significant increases in hemoglobin, hematocrit, PCS, and MCS over time, alongside decreases in platelet count and GSI. Compared with participants without HAND, those with HAND consistently exhibited lower hemoglobin, hematocrit, GAF, and GSI scores, and higher platelet counts and MCS scores across follow-up. These findings underscore the complex interplay between hematologic and mental health, substance use, and functional status in shaping neurocognitive outcomes among PWH. Targeting modifiable hematologic, behavioral, and psychosocial factors may help reduce HAND risk and improve long-term cognitive and functional outcomes. ClinicalTrials.gov ID: NCT01612169.